Longitudinal transcriptome analysis reveals distinct gene expression patterns in traditional Chinese medicine syndromes of upper respiratory tract infections - Zou, Hao; Huang, Changrui; Feng, Qinqi; Yu, Bang; Liu, Jian; Shu, Xinyang; Nie, Xiaolu; Zhang, Hongchun; Zou, Xiaohui (Frontiers in Genetics, 2024)
BackgroundWind-cold (WC) and Wind-heat (WH) are common syndromes of upper respiratory tract infections (URTIs) in traditional Chinese medicine (TCM), presenting different clinical features, but the transcriptomic changes associated with these syndromes remained unclear.Materials and MethodsPatients with WC and WH syndromes were recruited from outpatient unit, pharyngeal swabs were collected for pathogen detection. Peripheral blood samples were obtained on day 1 and day 6, with healthy volunteers as controls. Transcriptome sequencing was performed to identify differentially expressed genes and pathways associated with the two syndromes. Marker genes for each syndrome were identified, and a machine learning classifier was developed.ResultsA total of 124 samples from 34 WC, 30 WH patients, and 16 health controls were included in this study. No significant differences in etiological spectrum were observed between the syndromes. Both syndromes showed distinct gene expression profiles compared to health control. Gene enrichment analysis indicated that TGF-β and Wnt/β -catenin pathways were downregulated in the WH. The oxidative phosphorylation pathways were downregulated in WC cohort compared to the WH cohort. As the URTIs improved from day 1 to day 6, oxidative phosphorylation pathway activity returned to normal levels. The marker genes for WC and WH syndromes were identified and a random forest classifier was built, achieving an accuracy of 0.88.ConclusionWC and WH syndromes demonstrated distinct gene expression profiles, supporting more precise TCM diagnosis. WC syndrome is marked by mitochondrial dysfunction, while WH syndrome is characterized by downregulated TGF-β and Wnt/β-catenin pathways.